A Decision-Aided Situation Awareness Mechanism Based on Multiscale Dynamic Trust. (5th October 2015) - Li, Fangwei; Nie, Yifang; Zhu, Jiang; Zhang, Haibo; Liu, Fan
Abstract : Attacks are always seeking ways of exploiting any existing weakness in wireless network. The purpose of security situation awareness is to recognize, analyze, forecast, and handle the misbehaviors, assisting network management. Nevertheless, the appearance of ubiquitous network and the network convergence technology has made a challenge to realize network security and adaptation. Aiming at these research problems, this paper proposes a decision-aided situation awareness mechanism based on multiscale dynamic trust from the perspective of time and space, which can recognize misbehaviors and regard social network as the research object. We build trust and satisfaction based on Ebbinghaus forgetting regular and spatial correlations. This mechanism carries out decision making assessment through trust authenticity test, logicality test, and feedback parameters. In addition, load balance is used to avoid resource congestion. Simulation analysis demonstrates that compared with other trust mechanisms, this mechanism proposed in this paper can recognize and handle entity attacks more effectively, which is relatively eclectic and realistic in aspect of trust mensuration.